2017
DOI: 10.2134/agronj2016.11.0665
|View full text |Cite
|
Sign up to set email alerts
|

Allometric Method to Estimate Leaf Area Index for Row Crops

Abstract: Core Ideas A new allometric method was developed to estimate LAI for row crops. Good agreement resulted for four crops over multiple seasons. Best agreement resulted using GDD, plant population, and canopy height. Leaf area index (LAI) is critical for predicting plant metabolism, biomass production, evapotranspiration, and greenhouse gas sequestration, but direct LAI measurements are difficult and labor intensive. Several methods are available to measure LAI indirectly or calculate LAI using allometric methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 55 publications
1
19
2
Order By: Relevance
“…5). Overall, discrepancies were very similar to a previous study for cotton and grain sorghum, where the allometric model used to calculate LAI was developed and tested (Colaizzi et al, 2017). In the previous study, LAI measurements were also obtained at Bushland, Texas, but for crops planted in straight rows and usually irrigated by lateral move sprinklers.…”
Section: Allometric Lai Model Testsupporting
confidence: 81%
See 2 more Smart Citations
“…5). Overall, discrepancies were very similar to a previous study for cotton and grain sorghum, where the allometric model used to calculate LAI was developed and tested (Colaizzi et al, 2017). In the previous study, LAI measurements were also obtained at Bushland, Texas, but for crops planted in straight rows and usually irrigated by lateral move sprinklers.…”
Section: Allometric Lai Model Testsupporting
confidence: 81%
“…However, only canopy width (w C ), canopy height (h C ), and plant population measurements were available in the present study, and LAI measurements were available only in a few seasons and in a limited number of plots. Therefore, LAI was estimated by an allometric method that used plant population, h C , and cumulative growing degree days (Colaizzi et al, 2017).…”
Section: Tseb Model Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“… log()LAI=alog()DBH+b, where a and b are regression coefficients derived from field measured LAI and DBH for different species, height, and management practices. In many studies, LAI is estimated as a product of the leaf length and width for different plant types and ages (Baret et al, ; Colaizzi et al, ; Homem Antunes et al, ).…”
Section: Lai Field Measurementmentioning
confidence: 99%
“…As an alternative, Turner et al () suggested estimating LAI from the sapwood cross‐sectional area, because of their strong physiological relationship. Climatic variables, such as growing degree days and air temperature, have also been added to improve the model performance (Colaizzi et al, ; Yoshida et al, ). Although the approach is more commonly used for forests (Law et al, ; Vyas, et al, ), it has also been explored for crops (Colaizzi et al, ; Yoshida et al, ).…”
Section: Lai Field Measurementmentioning
confidence: 99%